Hormone Replacement Versus Natural Cycle Protocols of Endometrial Preparation for Frozen Embryo Transfer - Pan, Ye; Li, Bo; Wang, Ze; Wang, Ying; Gong, Xiaoshu; Zhou, Wenqing; Shi, Yuhua (Frontiers in Endocrinology, 2020)
Research question: Endometrial preparation is one of the most important steps for ensuring frozen embryo transfer success. However, there is no clear evidence that identifies an optimal endometrial preparation protocol for frozen embryo transfer. In addition, in studies that assessed which were the optimal endometrial preparation protocols, few analyzed the stage and the number of embryos. This study compared the pregnancy outcomes and perinatal obstetric complications of patients who were transferred two cleavage-stage frozen embryos with the natural cycle and those with the hormone replacement therapy cycle. Design: This study was a secondary analysis of data from a multicentre randomized controlled trial designed to compare the pregnancy and perinatal outcomes after frozen versus fresh embryo transfer. In this study, a total of 908 patients who were transferred two cleavage-stage embryos in the original trial were analyzed. Pregnancy outcomes and perinatal obstetric complications after the natural cycle and the hormone replacement therapy cycle were compared. Result: We found the endometrium in the natural group was significantly thicker than the hormone replacement therapy cycle group (p<0.01). The implantation rate (42.6% vs 37.3% p=0.049) showed a significant difference between the natural cycle group and the hormone replacement therapy cycle group. Compared to the natural cycle group, the hormone replacement therapy cycle group was associated with an increased risk of caesarean section (72.3% vs 84.5, p=0.009). Conclusion: The natural cycle protocol yielded thicker endometria, a higher implantation rate and a lower risk of caesarean section than the hormone replacement therapy protocol in the transfer of two cleavage-stage frozen embryos. The natural cycle protocol was the better endometrial preparation protocol for frozen embryo transfer.